Tin disulfide / graphene oxide / carbon nanotube composite material as well as preparation method and application thereof

By using graphene oxide and carbon nanotubes to recombinate with SnS2 in lithium-ion batteries, the problem of insufficient cyclic stability and rate performance of SnS2 in lithium-ion batteries is solved, and the electrical conductivity and cyclic stability are improved. It also simplifies the material preparation process and reduces costs.

CN119447224AActive Publication Date: 2025-02-14NANJING UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411444895.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-14
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

In the prior art, the cycling stability and rate performance of SnS2 in lithium-ion batteries are limited by volume expansion and electronic conductivity, and the preparation method of composite materials is complex, difficult to produce, poor safety, high cost, and mixing uniformity. insufficient.

Method used

The tin disulfide/graphene oxide/carbon nanotube composite is prepared by composite of graphene oxide and carbon nanotube with SnS2, and the tin disulfide/graphene oxide/carbon nanotube composite material is improved by deionized water dispersion, water bath reaction, polyvinyl alcohol freeze-drying and sintering, so as to improve its conductivity and Cyclic stability.

Benefits of technology

It realizes the preparation of composite materials with simple process, high safety and low cost, improves the conductivity and cycle stability of the materials, is suitable for lithium-ion battery electrodes, and has the potential for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447224A_ABST
    Figure CN119447224A_ABST
Patent Text Reader

Abstract

The invention discloses a tin disulfide / graphene oxide / carbon nanotube composite material and a preparation method and application thereof.The preparation method comprises the following steps that graphene oxide and carbon nanotubes are taken and dispersed in deionized water, and dispersion liquid is prepared; taking SnCl2. 2H2O crystals, dissolving the SnCl2. 2H2O crystals in the dispersion liquid, carrying out a water bath reaction, and carrying out suction filtration to prepare a mixed liquid; adding a polyvinyl alcohol solution into the mixed solution, quickly freezing for 4-6 hours through liquid nitrogen, and then freeze-drying; sintering at the temperature of 550-650 DEG C under the protection of nitrogen to prepare a tin dioxide / graphene oxide / carbon nanotube composite material; adding sublimed sulfur powder into the tin dioxide / graphene oxide / carbon nanotube composite material, and carrying out ball milling and uniform blending to obtain sulfur-doped powder; reacting the sulfur-doped powder under the protection of nitrogen at 400-500 DEG C, and keeping the temperature; the production process is low in cost, high in safety and good in dispersion effect, and the conductivity and cycling stability of the material serving as the negative electrode of the lithium ion battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a wave absorbing material and a preparation method thereof, in particular to a tin disulfide / graphene oxide / carbon nanotube composite material and a preparation method and application thereof. Background Art

[0002] In lithium-ion batteries, SnS2 achieves effective lithium ion insertion and extraction by generating intermediate compounds and metallic tin, showing a mass specific capacity far exceeding that of graphite negative electrodes (about 645 mAh / g). However, during the charge and discharge process, the large volume expansion rate and low electronic conductivity of SnS2 seriously restrict the maintenance of its cycle stability and the enhancement of its rate performance.

[0003] To this end, many studies have combined SnS2 with graphene and carbon nanotubes, using the flexible structure of carbon materials to buffer the volume expansion of sulfides, and using the high conductivity of carbon materials to enhance the overall conductivity of the electrode and improve the battery rate performance. However, the common material composite methods currently include: (1) Solvothermal method, which involves reducing graphene oxide and tin sulfide source under high temperature and high pressure conditions to generate composite materials; (2) Chemical vapor deposition method, which deposits SnS2 nanomaterials on the graphene surface through a complex CVD process to achieve material composite. These composite methods have complex physical and chemical processes, are difficult to produce and have poor safety, high costs, and the mixing uniformity needs to be further improved. Summary of the invention

[0004] Purpose of the invention: In order to overcome the deficiencies in the prior art, the purpose of the present invention is to provide a method for preparing a tin disulfide / graphene oxide / carbon nanotube composite material with simple process, high safety and scalable production. Another purpose of the present invention is to provide a tin disulfide / graphene oxide / carbon nanotube composite material with good conductivity and good cycle stability. Another purpose of the present invention is to provide an application of a tin disulfide / graphene oxide / carbon nanotube composite material in a lithium-ion battery electrode.

[0005] Technical solution: A method for preparing a tin disulfide / graphene oxide / carbon nanotube composite material according to the present invention comprises the following steps:

[0006] Step 1, dispersing graphene oxide and carbon nanotubes in deionized water to prepare a dispersion;

[0007] Step 2, taking SnCl2·2H2O crystals and dissolving them in the dispersion liquid, reacting them in a water bath, and filtering them to obtain a mixed liquid;

[0008] Step 3, adding polyvinyl alcohol (PVA) solution to the mixed solution, rapidly freezing by liquid nitrogen for 4 to 6 hours, and then freeze-drying for 72 to 100 hours;

[0009] Step 4, sintering at 550-650° C. under nitrogen protection to obtain a tin dioxide / graphene oxide / carbon nanotube composite material;

[0010] Step 5, adding sublimated sulfur powder to the tin dioxide / graphene oxide / carbon nanotube composite material, and ball milling and blending the mixture uniformly to obtain sulfur-doped powder;

[0011] Step six, reacting the sulfur-doped powder under nitrogen protection at 400-500° C. and keeping the temperature, to obtain a tin disulfide / graphene oxide / carbon nanotube composite material.

[0012] Furthermore, in step 1, the mass ratio of graphene oxide, carbon nanotubes, and deionized water is 1-10:1:1000-10000. The dispersion is stirred for 2 hours and ultrasonicated for 30 minutes, and repeated at least 10 times. Too high a concentration of graphene oxide and carbon nanotubes, and too short a stirring and ultrasonication time are not conducive to the effective dispersion of the dispersed substance in the dispersion.

[0013] Furthermore, in step 2, the mass ratio of SnCl2·2H2O crystals to deionized water is 1 to 5:250. The temperature of the water bath reaction is 70 to 90°C.

[0014] Furthermore, in step 3, the volume ratio of the PVA solution to the mixed solution is 1:20 to 30. The mass concentration of the PVA solution is 10%.

[0015] Furthermore, in step 5, the mass ratio of sublimated sulfur powder to tin dioxide / graphene oxide / carbon nanotube composite material is 3 to 8: 1. The ball milling speed is 200 to 300 rpm, and the time is 2 to 6 hours.

[0016] Furthermore, in step six, the insulation temperature is 200-300° C., the time is 6-10 hours, and the crucible is not covered during the insulation process.

[0017] The tin disulfide / graphene oxide / carbon nanotube composite material prepared by the method for preparing the tin disulfide / graphene oxide / carbon nanotube composite material of the present invention comprises tin disulfide nanosheets, graphene oxide, and carbon nanotubes, wherein the tin disulfide nanosheets are wrapped in graphene and carbon nanotube agglomerates. The crucible is covered during the reaction at 400-500°C.

[0018] The invention discloses an application of a tin disulfide / graphene oxide / carbon nanotube composite material in a lithium ion battery electrode.

[0019] Furthermore, the method comprises the following steps: mixing and dispersing the SnS2 / graphene oxide / carbon nanotube composite material, polyvinylidene fluoride and conductive carbon black in NMP, coating the mixture on the surface of copper foil, and cutting the mixture to obtain an electrode foil for lithium-ion batteries.

[0020] Preparation principle: The prepared SnS2 is a nanosheet structure, which is wrapped inside the carbon material or attached to its surface. The introduction of PVA plays a thickening role in the dispersion, and together with the rapid freezing + freeze-drying operation, it avoids the uneven composite of the material caused by the sedimentation of the dispersion. In addition, the addition of PVA can also maintain the precursor structure during the freeze-drying process and avoid the collapse of the structure. The uniform mixing of SnS2 in the carbon material improves its electronic conductivity as an electrode material. At the same time, the structural toughness of the carbon material also effectively buffers the volume expansion of SnS2 during the charge and discharge process, and improves the overall cycle stability of the material.

[0021] Beneficial effects: Compared with the prior art, the present invention has the following significant features:

[0022] 1. The production process is low-cost and highly safe. The whole process does not involve complex equipment and high-pressure reactions. It can effectively compound materials under normal pressure. It is convenient and practical, and has the potential for large-scale production.

[0023] 2. The dispersion effect is good. The uniform preparation of the composite material is achieved through rapid freezing + freeze-drying operation. The SnS2 nanosheets are effectively adhered to the surface of the carbon material or entangled inside the carbon material;

[0024] 3. The carbon material is effectively combined with SnS2 to improve the conductivity and cycle stability of the material as the negative electrode of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is the XRD spectrum of the tin disulfide / graphene oxide / carbon nanotube composite material of the present invention;

[0026] Figure 2 is a SEM image of the product obtained in Example 1 of the present invention;

[0027] Figure 3 is a TEM image of the product obtained in Example 1 of the present invention;

[0028] Figure 4 is a SEM image of the product obtained in Example 2 of the present invention;

[0029] Figure 5 is a TEM image of the product obtained in Example 2 of the present invention;

[0030] Figure 6 is a SEM image of the product obtained in Example 3 of the present invention;

[0031] Figure 7 is a TEM image of the product obtained in Example 3 of the present invention;

[0032] Figure 8 is a SEM image of the product obtained in Example 4 of the present invention;

[0033] Fig. 9 This is a TEM image of the product obtained in Example 4 of the present invention. DETAILED DESCRIPTION

[0034] Unless otherwise specified, the materials, reagents, instruments, etc. used in the following examples can be obtained from commercial sources. Experimental methods without specific conditions in the examples are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0035] Example 1

[0036] A method for preparing a SnS2 / graphene oxide / carbon nanotube composite material comprises the following steps:

[0037] (1) 200 mg of graphene oxide and 50 mg of carbon nanotubes were dispersed in 250 ml of deionized water to prepare a dispersion. During the dispersion process, stirring was performed for 2 hours and ultrasonication was performed for 30 minutes, and this process was repeated 10 times.

[0038] (2) 1.5 g of SnCl2·2H2O crystals were dissolved in the dispersion, reacted in a water bath at 90° C. for 2 hours, and then filtered to remove impurities, thereby preparing a mixed solution.

[0039] (3) 10 ml of a 10% polyvinyl alcohol (PVA) solution was added to the mixed solution, followed by rapid freezing by liquid nitrogen for 4 hours, followed by freeze drying for 96 hours.

[0040] (4) Sintering at 600°C for 2 hours under the protection of high-purity nitrogen to prepare a tin dioxide / graphene oxide / carbon nanotube composite material.

[0041] (5) Sublimated sulfur powder (whose mass is 5 times the mass of the composite material) is added to the tin dioxide / graphene oxide / carbon nanotube composite material, and the mixture is ball-milled at 250 rpm for 4 hours to obtain a uniformly sulfur-doped powder.

[0042] (6) The sulfur-doped powder was reacted at 400° C. for 3 hours under nitrogen protection (the crucible was covered during the reaction) to prepare a tin disulfide / graphene oxide / carbon nanotube composite material.

[0043] (7) The system was heated at 200° C. for 6 hours under a nitrogen atmosphere to remove excess sulfur powder in the tin disulfide / graphene oxide / carbon nanotube composite material system.

[0044] like Figure 1 , indicating the successful synthesis of the tin disulfide crystal structure. Figures 2-3 , tin disulfide nanosheets are wrapped in graphene / carbon nanotube clusters on a micrometer scale.

[0045] Example 2

[0046] A method for preparing a SnS2 / graphene oxide / carbon nanotube composite material comprises the following steps:

[0047] (1) 200 mg of graphene oxide and 50 mg of carbon nanotubes were dispersed in 250 ml of deionized water to prepare a dispersion. During the dispersion process, stirring was performed for 2 hours and ultrasonication was performed for 30 minutes, and this process was repeated 10 times.

[0048] (2) 2 g of SnCl2·2H2O crystals were dissolved in the dispersion, reacted in a water bath at 90°C for 2 hours, and then filtered to remove impurities, thereby preparing a mixed solution.

[0049] (3) 10 ml of a 10% polyvinyl alcohol (PVA) solution was added to the mixed solution, followed by rapid freezing by liquid nitrogen for 4 hours, followed by freeze drying for 96 hours.

[0050] (4) Sintering at 600°C for 2 hours under the protection of high-purity nitrogen to prepare a tin dioxide / graphene oxide / carbon nanotube composite material.

[0051] (5) Sublimated sulfur powder (whose mass is 5 times the mass of the composite material) is added to the tin dioxide / graphene oxide / carbon nanotube composite material, and the mixture is ball-milled at 250 rpm for 4 hours to obtain a uniformly sulfur-doped powder.

[0052] (6) The sulfur-doped powder was reacted at 400° C. for 3 hours under nitrogen protection (the crucible was covered during the reaction) to prepare a tin disulfide / graphene oxide / carbon nanotube composite material.

[0053] (7) The system was heated at 200° C. for 6 hours under a nitrogen atmosphere to remove excess sulfur powder in the tin disulfide / graphene oxide / carbon nanotube composite material system.

[0054] like Figure 1 , indicating the successful synthesis of the tin disulfide crystal structure. Figures 4-5 , tin disulfide nanosheets are wrapped in graphene / carbon nanotube clusters on a micrometer scale.

[0055] Example 3

[0056] A method for preparing a SnS2 / graphene oxide / carbon nanotube composite material comprises the following steps:

[0057] (1) 200 mg of graphene oxide and 50 mg of carbon nanotubes were dispersed in 250 ml of deionized water to prepare a dispersion. During the dispersion process, stirring was performed for 2 hours and ultrasonication was performed for 30 minutes, and this process was repeated 10 times.

[0058] (2) 2.5 g of SnCl2·2H2O crystals were dissolved in the dispersion, reacted in a water bath at 90° C. for 2 hours, and then filtered to remove impurities, thereby preparing a mixed solution.

[0059] (3) 10 ml of a 10% polyvinyl alcohol (PVA) solution was added to the mixed solution, followed by rapid freezing by liquid nitrogen for 4 hours, followed by freeze drying for 96 hours.

[0060] (4) Sintering at 600°C for 2 hours under the protection of high-purity nitrogen to prepare a tin dioxide / graphene oxide / carbon nanotube composite material.

[0061] (5) Sublimated sulfur powder (whose mass is 5 times the mass of the composite material) is added to the tin dioxide / graphene oxide / carbon nanotube composite material, and the mixture is ball-milled at 250 rpm for 4 hours to obtain a uniformly sulfur-doped powder.

[0062] (6) The sulfur-doped powder was reacted at 400° C. for 3 hours under nitrogen protection (the crucible was covered during the reaction) to prepare a tin disulfide / graphene oxide / carbon nanotube composite material.

[0063] (7) The system was heated at 200° C. for 6 hours under a nitrogen atmosphere to remove excess sulfur powder in the tin disulfide / graphene oxide / carbon nanotube composite material system.

[0064] like Figure 1 , indicating the successful synthesis of the tin disulfide crystal structure. Figures 6-7 , tin disulfide nanosheets are wrapped in graphene / carbon nanotube clusters on a micrometer scale.

[0065] Example 4

[0066] A method for preparing a SnS2 / graphene oxide / carbon nanotube composite material comprises the following steps:

[0067] (1) 200 mg of graphene oxide and 50 mg of carbon nanotubes were dispersed in 250 ml of deionized water to prepare a dispersion. During the dispersion process, stirring was performed for 2 hours and ultrasonication was performed for 30 minutes, and this process was repeated 10 times.

[0068] (2) 3 g of SnCl2·2H2O crystals were dissolved in the dispersion, reacted in a water bath at 90° C. for 2 hours, and then filtered to remove impurities, thereby preparing a mixed solution.

[0069] (3) 10 ml of a 10% polyvinyl alcohol (PVA) solution was added to the mixed solution, followed by rapid freezing by liquid nitrogen for 4 hours, followed by freeze drying for 96 hours.

[0070] (4) Sintering at 600°C for 2 hours under the protection of high-purity nitrogen to prepare a tin dioxide / graphene oxide / carbon nanotube composite material.

[0071] (5) Sublimated sulfur powder (whose mass is 5 times the mass of the composite material) is added to the tin dioxide / graphene oxide / carbon nanotube composite material, and the mixture is ball-milled at 250 rpm for 4 hours to obtain a uniformly sulfur-doped powder.

[0072] (6) The sulfur-doped powder was reacted at 400° C. for 3 hours under nitrogen protection (the crucible was covered during the reaction) to prepare a tin disulfide / graphene oxide / carbon nanotube composite material.

[0073] (7) The system was heated at 200° C. for 6 hours under a nitrogen atmosphere to remove excess sulfur powder in the tin disulfide / graphene oxide / carbon nanotube composite material system.

[0074] like Figure 1 , indicating the successful synthesis of the tin disulfide crystal structure. Figures 8-9 , tin disulfide nanosheets are wrapped in graphene / carbon nanotube clusters on a micrometer scale.

[0075] Example 5

[0076] A method for preparing a SnS2 / graphene oxide / carbon nanotube composite material comprises the following steps:

[0077] (1) 50 mg of graphene oxide and 50 mg of carbon nanotubes were dispersed in 50 ml of deionized water to prepare a dispersion. During the dispersion process, stirring was performed for 2 hours and ultrasonication was performed for 30 minutes, and this process was repeated 10 times.

[0078] (2) 0.2 g of SnCl2·2H2O crystals were dissolved in the dispersion, reacted in a water bath at 70° C. for 2 hours, and then filtered to remove impurities, thereby preparing a mixed solution.

[0079] (3) 2.5 ml of a 10% polyvinyl alcohol (PVA) solution was added to the mixed solution, followed by rapid freezing with liquid nitrogen for 4 hours and subsequent freeze drying for 96 hours.

[0080] (4) Sintering at 550°C for 2 hours under the protection of high-purity nitrogen to prepare a tin dioxide / graphene oxide / carbon nanotube composite material.

[0081] (5) Sublimated sulfur powder (whose mass is 3 times the mass of the composite material) is added to the tin dioxide / graphene oxide / carbon nanotube composite material, and the mixture is ball-milled at 200 rpm for 6 hours to obtain a uniformly sulfur-doped powder.

[0082] (6) The sulfur-doped powder was reacted at 500° C. for 3 hours under nitrogen protection (the crucible was covered during the reaction) to prepare a tin disulfide / graphene oxide / carbon nanotube composite material.

[0083] (7) The system was heated at 300° C. for 8 hours under a nitrogen atmosphere to remove excess sulfur powder in the tin disulfide / graphene oxide / carbon nanotube composite material system.

[0084] Example 6

[0085] A method for preparing a SnS2 / graphene oxide / carbon nanotube composite material comprises the following steps:

[0086] (1) 500 mg of graphene oxide and 50 mg of carbon nanotubes were dispersed in 500 ml of deionized water to prepare a dispersion. During the dispersion process, stirring was performed for 2 hours and ultrasonication was performed for 30 minutes, and this process was repeated 10 times.

[0087] (2) 10 g of SnCl2·2H2O crystals were dissolved in the dispersion, reacted in a water bath at 80° C. for 2 hours, and then filtered to remove impurities, thereby preparing a mixed solution.

[0088] (3) 16.7 ml of a 10% polyvinyl alcohol (PVA) solution was added to the mixed solution, followed by rapid freezing by liquid nitrogen for 4 hours and subsequent freeze drying for 96 hours.

[0089] (4) Sintering at 650°C for 2 hours under the protection of high-purity nitrogen to prepare a tin dioxide / graphene oxide / carbon nanotube composite material.

[0090] (5) Sublimated sulfur powder (whose mass is 8 times the mass of the composite material) is added to the tin dioxide / graphene oxide / carbon nanotube composite material, and the mixture is ball-milled at 300 rpm for 2 hours to obtain a uniformly sulfur-doped powder.

[0091] (6) The sulfur-doped powder was reacted at 450° C. for 3 hours under nitrogen protection (the crucible was covered during the reaction) to prepare a tin disulfide / graphene oxide / carbon nanotube composite material.

[0092] (7) The system was heated at 250 °C for 10 hours under a nitrogen atmosphere to remove excess sulfur powder in the tin disulfide / graphene oxide / carbon nanotube composite material system.

[0093] Application Example 1

[0094] Accurately weigh 800 mg of the SnS2 / graphene oxide / carbon nanotube composite material prepared in Example 1, 100 mg of PVDF, and 100 mg of conductive carbon black, disperse them in 4 mL of NMP, and apply them on the surface of a 20-micron thick copper foil after magnetic stirring for 24 hours to obtain the required pole piece. High-purity lithium sheets and microporous polyethylene (PE) membranes are used as the anode and diaphragm of the battery. 1M LiPF6 is dissolved in a mixed solution of ethyl carbonate (EC) and dimethyl carbonate (DMC) in a volume ratio of 1:1 as an electrolyte. The entire assembly of CR2032 button batteries is carried out in a glove box filled with argon, and the water and oxygen concentration in the glove box is controlled below 0.1 ppm. Each battery contains 100 microliters of electrolyte.

[0095] Application Example 2

[0096] Except that the SnS2 / graphene oxide / carbon nanotube composite material is replaced by the material of Example 2, the remaining steps are the same as those of Application Example 1.

[0097] Application Example 3

[0098] Except that the SnS2 / graphene oxide / carbon nanotube composite material is replaced by the material of Example 3, the remaining steps are the same as those of Application Example 1.

[0099] Application Example 4

[0100] Except that the SnS2 / graphene oxide / carbon nanotube composite material is replaced by the material of Example 4, the remaining steps are the same as those of Application Example 1.

[0101] The lithium-ion batteries obtained in Examples 1 to 4 were tested for performance using a battery testing system, with a test voltage window of 0 to 3 V. The results are shown in Table 1. The number of stable cycles refers to the number of stable charge and discharge times of the battery, with one charge or discharge process being counted as one cycle, and the discharge capacity refers to the mass specific capacity of the battery after 100 charge and discharge cycles at a current density of 500 mA / g.

[0102] Table 1 Performance data of lithium-ion batteries obtained from application examples 1 to 4

[0103] Cycle stability number of turns Discharge capacity (mAh / g) Application Example 1 100 561 Application Example 2 100 612 Application Example 3 100 557 Application Example 4 100 463

[0104] It can be seen from Table 1 that the discharge capacity of the battery in Example 2 is the highest. Therefore, among the above embodiments, Example 2 is the optimal embodiment.

[0105] Comparative Example 1

[0106] The remaining steps of this comparative example are the same as those of Example 2, except that the mass concentration of PVA is replaced with 5%. A battery is made according to the method of Application Example 1. It is found that the dispersion is prone to sedimentation, and the macroscopic structure of the material collapses significantly after freeze-drying. The cycle stability of the battery is poor during the cycle.

[0107] Comparative Example 2

[0108] The remaining steps of this comparative example are the same as those of Example 2, except that the mass concentration of PVA is replaced with 15%. A battery was made according to the method of Application Example 1, and it was found that PVA could not be effectively dissolved in the system.

[0109] Comparative Example 3

[0110] The remaining steps of this comparative example are the same as those of Example 2, except that PVA is replaced by sodium carboxymethyl cellulose (CMC). A battery is made according to the method of Application Example 1. It is found that the dispersion effect of the dispersion is close to that of the PVA system, but the collapse of the macroscopic structure of the material after freeze-drying is more obvious. The cycle stability of the battery is poor during the cycle.

[0111] Comparative Example 4

[0112] The remaining steps of this comparative example are the same as those of Example 2, except that the SnCl2·2H2O crystals are replaced with stannous acetate (Sn(CH3COO)2). A battery was prepared according to the method of Application Example 1. It was found that the battery was difficult to dissolve during the preparation of the dispersion, and the mass specific capacity of the material after being prepared as an electrode material was low.

[0113] Comparative Example 5

[0114] The remaining steps of this comparative example are the same as those of Example 2, except that step (3) is replaced by rapid freezing by liquid nitrogen for 8 hours, followed by freeze drying for 48 hours. A battery is made according to the method of Application Example 1, and it is found that there is no significant difference compared with the situation in Application Example 1, but the test time is increased.

Claims

1. A method for preparing a tin disulfide / graphene oxide / carbon nanotube composite material, characterized in that: The following steps are involved: Step 1, dispersing graphene oxide and carbon nanotubes in deionized water to prepare a dispersion; Step 2, taking SnCl2·2H2O crystals and dissolving them in the dispersion liquid, reacting them in a water bath, and filtering them to obtain a mixed liquid; Step 3, adding polyvinyl alcohol solution to the mixed solution, rapidly freezing by liquid nitrogen for 4 to 6 hours, and then freeze-drying for 72 to 100 hours; Step 4, sintering at 550-650° C. under nitrogen protection to obtain a tin dioxide / graphene oxide / carbon nanotube composite material; Step 5, adding sublimated sulfur powder to the tin dioxide / graphene oxide / carbon nanotube composite material, and ball milling and blending the mixture uniformly to obtain sulfur-doped powder; Step six, reacting the sulfur-doped powder under nitrogen protection at 400-500° C. and keeping the temperature, to obtain a tin disulfide / graphene oxide / carbon nanotube composite material.

2. The method for preparing a tin disulfide / graphene oxide / carbon nanotube composite material according to claim 1, characterized in that: In the step 1, the mass ratio of graphene oxide, carbon nanotubes and deionized water is 1-10:1:1000-10000.

3. The method for preparing a tin disulfide / graphene oxide / carbon nanotube composite material according to claim 1, characterized in that: In the step 2, the mass ratio of SnCl2·2H2O crystals to deionized water is 1 to 5:

250.

4. The method for preparing a tin disulfide / graphene oxide / carbon nanotube composite material according to claim 1, characterized in that: In the step 2, the temperature of the water bath reaction is 70-90°C.

5. The method for preparing a tin disulfide / graphene oxide / carbon nanotube composite material according to claim 1, characterized in that: In the step 3, the volume ratio of the PVA solution to the mixed solution is 1:20-30.

6. The method for preparing a tin disulfide / graphene oxide / carbon nanotube composite material according to claim 1, characterized in that: In the step 5, the mass ratio of the sublimated sulfur powder to the tin dioxide / graphene oxide / carbon nanotube composite material is 3 to 8:

1.

7. The method for preparing a tin disulfide / graphene oxide / carbon nanotube composite material according to claim 1, characterized in that: In the step 5, the rotation speed of the ball mill is 200 to 300 rpm, and the time is 2 to 6 hours.

8. The method for preparing a tin disulfide / graphene oxide / carbon nanotube composite material according to claim 1, characterized in that: In the step six, the insulation temperature is 200-300° C. and the time is 6-10 hours.

9. The tin disulfide / graphene oxide / carbon nanotube composite material obtained by the method for preparing a tin disulfide / graphene oxide / carbon nanotube composite material according to any one of claims 1 to 8, characterized in that: The invention comprises tin disulfide nanosheets, graphene oxide and carbon nanotubes, wherein the tin disulfide nanosheets are wrapped in graphene and carbon nanotube clusters.

10. Use of the tin disulfide / graphene oxide / carbon nanotube composite material according to claim 9 in lithium ion battery electrodes.

Citation Information

Patent Citations

  • Preparation method of graphene-tin dioxide nanoparticle three-dimensional foam composite material

    CN103482616A

  • Preparation method of SnO2 / SnS2 / CNTs (carbon nanotubes) electrode material for lithium ion battery negative electrode

    CN105702933A

  • Tin dioxide-graphene-carbon nano tube flexible cathode material as well as preparation method and application thereof

    CN108807958A

  • Tin diselenide / tin oxide-rGO nano composite negative electrode material and preparation method thereof

    CN111180707A

  • Preparation method of SnS2 / SnO2 heterojunction nanosheet array photo-anode

    CN113073355A